2013
DOI: 10.5888/pcd10.120148
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Electronic Health Record-Based Screening, Prevention, and Management of Diabetes in New York City

Abstract: To address the increasing burden of diabetes in New York City, we designed 2 electronic health records (EHRs)-facilitated diabetes management systems to be implemented in 6 primary care practices on the West Side of Manhattan, a standard system and an enhanced system. The standard system includes screening for diabetes. The enhanced system includes screening and ensures close patient follow-up; it applies principles of the chronic care model, including community–clinic linkages, to the management of patients n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In addition, the quality improvement initiative based upon this strategy reduced the rate of being at risk for undiagnosed hypertension over a 30-month period by more than 72% (1.1/100 to 0.3/100). Prior studies have used algorithms to screen EHRs for chronic illnesses, including chronic kidney disease 26 and diabetes 27 based upon data such as estimated glomerular filtration rate or glycosylated hemoglobin. Diagnosing hypertension based upon EHR data, however, presents an additional challenge caused by variability in office-based blood pressure measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the quality improvement initiative based upon this strategy reduced the rate of being at risk for undiagnosed hypertension over a 30-month period by more than 72% (1.1/100 to 0.3/100). Prior studies have used algorithms to screen EHRs for chronic illnesses, including chronic kidney disease 26 and diabetes 27 based upon data such as estimated glomerular filtration rate or glycosylated hemoglobin. Diagnosing hypertension based upon EHR data, however, presents an additional challenge caused by variability in office-based blood pressure measurements.…”
Section: Discussionmentioning
confidence: 99%
“…We developed and implemented a pre-diabetes management program in an urban primary care setting [10], offered a structured training for the program that targeted both providers and staff, and evaluated whether the providers' and staff's perceived ability to manage patients with pre-diabetes improved after the training and then again after working within this program for six months. This study is the first to focus on satisfaction with a pre-diabetes management program reported by both providers and office staff.…”
Section: Discussionmentioning
confidence: 99%
“…We recently implemented a pre-diabetes screening and management program in a large primary health care network as part of a New York City's patient-centered medical home (PCMH) initiative [10]. PCMH is an application of the chronic care model, which focuses on a shift in primary care delivery to prevention, early detection, and patientcentered interventions [11].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment for substance use disorder: opportunities and challenges under the affordable care act 28 2013, Maryland (USA) Clinical Trial 11. Expansion of electronic health record-based screening, prevention, and management of diabetes in New York City 29 2013 diseases, 25% reduction in admissions due to diabetes; reduction of 38% of emergency calls to patients with asthma and 50% reduction of occurrence of absenteeism due to arthritis. 36,37 A cohort transverse epidemiological prospective study, conducted by a team of cardiologists and oncologists Executive Master in Business Administration at the University of Parana, 38 compared a group of patients monitored by a CDMCP with subjects without CDMCP assistance since 2010 to 2012.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the following limits were imposed: i) text availability: free full text; ii) publication dates: 5 years; and iii) species: human, with the exclusion of 94 studies, for a total of 14 studies useful for the revision (Table 2). [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] …”
Section: Methodsmentioning
confidence: 99%